An Analysis of the Impact of Implementing Ministry of Health Regulation No. 24 of 2022 on Medical Records on the Quality of Healthcare Services - Wasliati, Balqis (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Healthcare quality is a key indicator in assessing the performance of health systems worldwide, and medical record management plays a crucial role in achieving high-quality healthcare. Objective: This study aims to analyze the impact of the implementation of Ministry of Health Regulation No. 24 of 2022 on medical records on healthcare quality. Research Methods: This study employs a cross-sectional design with a sample of 120 healthcare workers. Data were collected through questionnaires and medical record audits, then analyzed using univariate analysis for data description and bivariate analysis with Chi-Square. Results: Most respondents at RS Grandmed Lubuk Pakam were aware of Ministry of Health Regulation No. 24 of 2022 (85%), but only 72% felt its implementation was effective. Healthcare quality was generally satisfactory (83.3%), though there were some errors in medical records (11.7%). The analysis revealed a significant relationship between the implementation of the regulation and healthcare quality (? = 0.478, p = 0.002). Training for healthcare workers and available infrastructure had a significant impact on healthcare quality, while work experience did not. Conclusion: The implementation of Ministry of Health Regulation No. 24 of 2022 at RS Grandmed Lubuk Pakam has a positive impact on healthcare quality, despite challenges related to infrastructure and training. The policy has improved patient satisfaction but requires further improvements in facilities, training, and time management for greater effectiveness. Routine evaluation is necessary to ensure the continued enhancement of healthcare quality.